Gambaran Dislipidemia Pada Pasien Diabetes Melitus Tipe 2 di RSUD Doris Sylvanus Palangka Raya - Kevin Pratama Masal (Malahayati Nursing Journal, 2023)
ABSTRACT Abnormal lipid profiles are still common in patients with type 2 diabetes melitus. This can lead to complications of cardiovascular disease and other diseases that can increase morbidity and mortality. This study aims to describe dyslipidemia in patients with type 2 diabetes melitus at Doris Sylvanus Hospital. This research is a descriptive study with a cross-sectional method, which was conducted at Doris Sylvanus Hospital using medical record data of patients with type 2 diabetes melitus totaling 55 patients as research subjects. An overview of the lipid profile of type 2 DM patients at Doris Sylvanus Hospital was obtained through patient medical record data for the period September - November 2022, namely the average cholesterol level was 232.95 mg/dL, the average HDL level was 40.76 mg/dL, the average LDL level was 172.62 mg/dL and the average triglyceride level was 212.95 mg/dL. The prevalence of Type 2 DM patients with elevated cholesterol levels at Doris Sylvanus General Hospital in the period October - December 2021 was 76.4%, low HDL levels were 50.9%, high LDL levels were 85.5% and levels high triglycerides, namely as much as 69.1%. Keywords: Lipid Profiles, Type 2 Diabetes Melitus  ABSTRAK Profil lipid yang abnormal masih sering ditemui pada pasien dengan diabetes melitus tipe 2. Hal ini dapat mengakibatkan komplikasi penyakit kardiovaskular dan penyakit lainnya sehingga dapat meningkatkan angka morbiditas dan mortalitas. Penelitian ini bertujuan untuk mengetahui gambaran dislipidemia pada pasien diabetes melitus tipe 2 di RSUD Doris Sylvanus. Penelitian ini merupakan penelitian deskriptif dengan metode potong-lintang yang dilakukan di RSUD Doris Sylvanus selama bulan September-November 2022 dengan menggunakan data rekam medik pasien dengan diabetes melitus tipe 2.  Hasil penelitian terhadap 55 pasien DM tipe 2 didapatkan rerata kadar kolesterol total sebesar 232,95 mg/dL, rerata kadar HDL sebesar 40,76 mg/dL, rerata kadar LDL sebesar 172,62 mg/dL dan rerata kadar trigliserida sebesar 212,95 mg/dL. Sebagian besar pasien DM tipe 2 mengalami gangguan profil lipid, yaitu 42 (76,4%) pasien dengan peningkatan kolesterol total, 47 (85,5%) pasien dengan peningkatan kadar LDL, 38 (69,1%) pasien dengan peningkatan kadar trigliserida dan 28 (50,9%) pasien dengan kadar HDL yang rendah. Kata Kunci: Lipid, Diabetes Melitus Tipe 2